Isosexual precocious pseudopuberty during mitotane treatment in a child with adrenocortical carcinoma: A case report - Maria Riedmeier; Sonir Antonini; Clemens Benoit; Cheri L. Deal; Fassnacht Martin; Bonald C. Figueiredo; Elmas Nazli Gonc; Christoph Härtel; Jan Idkowiak; Max Kurlbaum; Ronald de Krijger; Raul C. Ribeiro; et al. (Elsevier, 2024)
Background: Mitotane is employed as adjuvant therapy in managing adrenocortical carcinoma in pediatric patients. While various adverse effects, such as estrogen-like manifestations, are well-documented in adults, there is limited knowledge regarding pediatric-specific toxicity. This report details an uncommon case of isosexual precocious pseudopuberty induced during childhood due to the estrogen-like effects of mitotane. Case report: A 2.8-year-old female diagnosed with adrenocortical carcinoma (pT4 pN0 M0) underwent adjuvant treatment with mitotane and cytotoxic chemotherapy following incomplete resection (tumor stage III). Approximately eight months into mitotane treatment, she exhibited signs of puberty (Tanner stage 2), including progressive breast development, uterine enlargement, vaginal discharge, and an advancement of bone age by nearly two years. Gonadotrophin-dependent puberty and endogenous estrogen production were ruled out. The precocious pseudopuberty was attributed to previously reported estrogen-like effects of mitotane therapy. Subsequent administration of the aromatase inhibitor anastrozole in combination with mitotane led to a reduction in clinical signs of puberty. Conclusion: Monitoring for estrogen-like effects of mitotane is crucial, particularly in pre-pubertal children, to avert potentially irreversible changes associated with precocious pseudopuberty. Aromatase inhibitors may serve as a prompt therapeutic option, enabling the continuation of mitotane treatment.